Media-induced anxiety and cultural coping mechanisms during COVID-19 in Surabaya - Ida, Rachmah; Kinasih, Sri Endah; Puspa, Ratih; Romadhona, Mochamad Kevin (Master of Communication Science Program, Universitas Diponegoro, 2025)
This study investigates the socio-psychological reactions and coping strategies of urban outskirts residents in Surabaya, Indonesia, amidst the COVID-19 pandemic. Through a combination of quantitative surveys and qualitative interviews with 100 respondents, the research explores how individuals perceive and respond to the abundance of information about COVID-19, including its origins, death tolls, and misinformation on mainstream and social media platforms. While some respondents feel devastated by the information overload, others surrender to the belief that the pandemic is destined by a higher power. Coping mechanisms vary, with some focusing on boosting immunity through vitamins and herbal drinks, engaging in cultural rituals, or turning to religious spirituality. The study draws on perspectives from Communication and Health Anthropology to offer a comprehensive understanding of local practices in response to the pandemic, contributing to broader global Sustainable Development Goals.